A Practical and Rational Strategy for Improved Optical and Electrical Properties: Reduced Graphene Oxide/Polycarbazole Based Hybrid Nanocomposite - Güzel, Merve (Fırat University, 2024)
Rapid advances in science and technology increase the interest in nanocomposites day by day. In recent years, nanocomposite materials formed by the combination of carbon-based nanostructures and conductive polymer (CP) have attracted considerable attention. The combination of the advantages of both materials under one roof provides versatile functionality to nanocomposites. The present study includes the preparation of a new nanocomposite material based on the excellent association between CP and reduced graphene oxide (rGO). In this context, firstly, a new rGO/CP hybrid nanocomposite polymer film was obtained by coating carbazole-based monomer (coded PFA-Cz) on the indium tin oxide (ITO) electrode modified with rGO by electrochemical polymerization method. The optical and electrical properties of this nanocomposite film were investigated comparatively with the homopolymer. The nanocomposite film exhibited interesting synergistic properties based on the combination of the redox properties of the homopolymer with the good electronic conductivity of rGO. This combination can be considered as a practical and rational strategy for obtaining nanocomposite materials with improved electrical and optical properties.

Bilim ve teknolojideki hızlı ilerlemeler, nanokompozitlere olan ilgiyi her geçen gün arttırmaktadır. Son yıllarda özellikle karbon temelli nanoyapılar ile iletken polimerin (CP) kombinasyonu ile oluşturulan nanokompozitler malzemeler oldukça dikkat çekmektedir. Her iki malzemenin avantajlarının tek bir çatı altında toplanması, nanokompozitlere çok yönlü işlevsellik kazandırmaktadır. Mevcut çalışma, CP ve indirgenmiş grafen oksit (rGO) arasındaki mükemmel birlikteliğe dayalı yeni bir nanokompozit malzemesinin eldesini içermektedir. Bu kapsamda, ilk olarak, rGO ile modifiye edilen indiyum kalay oksit (İTO) elektrodun üzerinde karbazol bazlı monomerin (PFA-Cz kodlu) elektrokimyasal polimerizasyon yöntemiyle kaplanmasıyla yeni bir rGO/CP hibrit nanokompozit polimer film elde edilmiştir. Bu nanokompozit filmin optik ve elektriksel özellikleri, homopolimer ile karşılaştırmalı olarak incelenmiştir. Nanokompozit film, homopolimerin redoks özellikleri ile rGO’nun iyi elektronik iletkenliğinin birleşimine dayanan ilginç sinerjik özellikler sergilemiştir. Bu kombinasyon, gelişmiş elektriksel ve optik özelliklere sahip nanokompozit malzemeler eldesi için pratik ve rasyonel bir strateji olarak değerlendirilebilir.
Gelişmiş Optik ve Elektriksel Özellikler İçin Pratik ve Rasyonel Bir Strateji: İndirgenmiş Grafen Oksit/ Polikarbazol Bazlı Hibrit Nanokompozit
Keywords: Materials Science and Technologies; Malzeme Bilimi ve Teknolojileri; Polymer Science and Technologies; Polimer Bilimi ve Teknolojileri; Polymer Technologies; Polimer Teknolojisi